Increase interest in scientific writing through Mendeley workshop - Faruq Alhasbi; Abyanuddin Al Java; Afifah Anwari Mattali Ahmad; Rafi Ilham Hakim (Community Empowerment, 2024)
Creating an academic atmosphere for students can be achieved through various means, one of which involves writing scientific papers. Presently, students are required to actively engage in this practice. However, not many students grasp the correct method of citing and compiling a bibliography. The objective of this activity is to enhance interest and proficiency in utilizing Mendeley. The training was conducted in two phases: initially, presenting materials concerning the introduction and benefits of the application, followed by practical exercises in operating Mendeley, from entering reference data to implementing citations in Microsoft Word documents. Consequently, participants of the training have experienced the advantage of effortlessly managing references for their scientific papers. Furthermore, workshop attendees have expressed increased enthusiasm towards writing and undertaking scientific assignments and projects, as Mendeley eliminates the inconvenience of organizing bibliographies.